Szok kulturowy w ujęciu deskrypcyjno-eksplikacyjnym - Mróz, Joanna (Culture shock viewed from a descriptive-explicative perspective, 2006)
The problem of culture shock in everyday life of expatriate is presented in the paper. At first the terms of expatriate and the process of cultural adjustment are defined. Following the experience of culture shock and the various responses to it are discussed. Finally the shock of returning home is presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 390-398